Investigação da saúde mental e da qualidade de vida de estudantes universitários de uma Universidade Pública federal - Toledo, Tullio Pieroni [UNIFESP] (2015)
The entry and permanence at the university represent a significant transition in life. The establishment of new affective bonds, hours of study, autonomy and expectations about career are examples of changes. The main goal of this study was to evaluate the quality of life and mental health of college students. The specific objectives were to raise the socioeconomic and cultural profile of college students; compare the dimensions of quality of life between course and gender; compare levels of depression, anxiety and stress among course and gender; identify data on physical activity and sports; contribute for formulation of future guidelines for quality of life and mental health programs. It is a cross-sectional study, quantitative, intentional sampling. The study was approved by the Ethics Committee of the Federal University of São Paulo (691,414). The sample consisted of 484 students of Psychology, Nutrition, Physical Therapy, Occupational Therapy, Physical Education, Bict-Sea and Medicine of a federal public university. Instruments: Socioeconomic and Cultural Questionnaire of students (Fonaprace); Economic Classification; Quality of Life (WHOQOL - BREF); Depression Anxiety Stress Scale - 21 (DASS- 21); International Physical Activity Questionnaire - IPAQ. Results: The sample consisted mostly of female students, single and not working. Male individuals obtained the higher mean values for quality of life, as well as were more active. The students had a higher incidence of anxiety, stress and depression. 31.8% of the sample showed clinically relevant levels for anxiety, stress and 39.0% to 29.5% for depression. The nutrition and medicine courses revealed the highest average for quality of life, while the lowest rates were observed in psychology courses and occupational therapy. 52% of students attributed the low academic performance to emotional issues. The anxiety was mentioned by 82.2% as the main variable that interfered in academic performance. The contingencies of university has significant impact on quality of life and mental health and that public policies of access and permanence in higher education should consider such issues in the development of their actions